(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To evaluate the results of laparoscopic surgical techniques combined transanal onestage endorectal pull-through, the treatment of Hirschsprung’s disease in children. Methods: Including 26 patients of HD (21 males, 5 females) with distal colon aganglionosis were considered candidates for laparoscopic techniques combined transanal one-stage endorectal pull-through from 1/2018 to 8/2022. Prospective studies with follow-up and re-examination of postoperative anal dilatation. The percentage of patients with good postoperative defecation function was 87.4%, only 12.6% was moderate and there was no poor type. Results: The median age was 11,5 months (ranging from 1 to 12 years old). The mean operative time was 158 ± 49 min. No conversion to an open operation was required. The average hospitalization time was 8,5 ± 3,5 days. There were no intraoperative or perioperative complications. Long term follow-up results were obtained from 24 patients. Conclusion: Laparoscopic surgical techniques combined transanal one-stage endorectal pullthrough, the treatment of Hirschsprung’s disease is safe and effective, can solve all very high and can be alternative for assisted laparotomy.